Desenvolvimento e avaliação de novos métodos de digestão/descontaminação de escarro para cultura de micobactérias - Fontana, Gerson (2019)
Rapid and accurate diagnosis and appropriate treatment for people with pulmonary tuberculosis are the main pillars for the control of this disease. Culture of mycobacteria is considered the gold standard for the diagnosis of tuberculosis, but contamination of culture media is one of the main problems that interferes with the isolation of mycobacteria in the laboratory routine, impairing and prolonging the diagnosis, consequently delaying the start of treatment and increasing the risks of transmission. In an attempt to reduce contamination in culture exams, this study aims to develop and evaluate new direct methods of sputum digestion / decontamination for culture of mycobacteria, using different decontaminants, being divided into three phases. In the first phase, it was performed an analysis of the interference of the reagents on the viability of Mycobacterium tuberculosis (MTB). In the second phase, direct methods were compared using sodium hydroxide (NaOH), chlorhexidine (CHX) and OMNIGene®. In the third phase, modifications were made to the direct methods to include fluidification and neutralization steps, as well as evaluation of different exposure times of reagents, in order to optimize the developed methods. The results demonstrated that CHX interferes less than NaOH on MTB viability and that a direct decontamination method with CHX 7% (1:10 ratio) for 15 minutes, with sample fluidification and reagent neutralization steps, provide equivalent results to the standard direct method with NaOH 4%. In all tests performed with OMNIGene® the results were similar to the standard NaOH method. With this study, it was possible to develop and evaluate two new direct methods of sputum digestion / decontamination for seeding in solid culture media and isolation of mycobacteria using CHX and OMNIGene®